2011
DOI: 10.3109/17435390.2011.579634
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized CuO, TiO2and ZnO affectXenopus laevisdevelopment

Abstract: The teratogenic potential of commercially available copper oxide (CuO), titanium dioxide (TiO2) and zinc oxide (ZnO) nanoparticles (NPs) was evaluated using the standardized FETAX test. After characterization of NP suspensions by TEM, DLS and AAS, histopathological screening and advanced confocal and energy-filtered electron microscopy techniques were used to characterize the induced lesions and to track NPs in tissues. Except for nCuO, which was found to be weakly embryolethal only at the highest concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 47 publications
3
67
1
Order By: Relevance
“…The authors suggest that TiO 2 NPs do not affect survival of X. laevis embryos, even at very high concentrations (Bacchetta et al, 2012;Birhanli et al, 2014). However, our results showed that Mn-doped TiO 2 NPs were slightly lethal in X. laevis embryos.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The authors suggest that TiO 2 NPs do not affect survival of X. laevis embryos, even at very high concentrations (Bacchetta et al, 2012;Birhanli et al, 2014). However, our results showed that Mn-doped TiO 2 NPs were slightly lethal in X. laevis embryos.…”
Section: Discussioncontrasting
confidence: 59%
“…It is suggested that aggregation of TiO 2 NPs may play an important role in the adverse effects due to the size and shape of nanoparticles, and these characteristics may also determine their toxic potential (Sharma, 2009;Miseljic and Olsen, 2014). Recent data show that TiO 2 NPs may not be toxic or are slightly to moderately toxic to fish and amphibians (Hao et al, 2009;Bacchetta et al, 2012). Therefore, their indirect role on mortality and physiology in aquatic organisms, such as fish and amphibians, due to some interactions with different kinds of organic pollutants in aquatic ecosystems has come into greater prominence.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In vivo experiments have been reported to further support the toxicity of MNPs (dysfunctions of the intestinal apparatus in embryonic zebra fish models, defects in the embryonic development of Xenopus laevis, phenotypic modifications in the progeny of Drosophila melanogaster and a decrease in body weight, red blood cells, hematocrit and DNA damage in mice). [24][25][26][27][28] The in vivo studies and the potential effects on public health and ecosystems are key to understanding the real applicability of a delivery strategy. Animal welfare, ethical issues and economics have rendered fundamental use of in vivo assays on invertebrates.…”
Section: Literature Is Overloaded Of Examples Of In Vitro Experimentsmentioning
confidence: 99%
“…Teratogenic effects are assessed by determining their influences on mortality, malformation, and growth inhibition, effects that clearly indicate developmental toxicity. This assay has been used to investigate teratogens and developmental toxicants that negatively affect human health and the ecosystem (18,19). FETAX is appropriate for the screening of chemicals (including nanomaterials), evaluating biotransformation, and can serve as a model of limb development.…”
Section: Introductionmentioning
confidence: 99%